Immunization Status Relationships: DPT-HB-HIB with Pneumonia in Age 12-24 Months at Babakan Sari Community Health Center Bandung - Benedika Mardewi Iswari (Universitas Muhammadiyah Malang, 2017)
Pneumonia was a high of mortality caused in toddlers in Indonesia. Toddlers mortality rate in Indonesia was high at 15.5%. In 2013, the amount of pneumonia in toddler (12-24 months) in Babakan Sari community health center were 1,496  from 11,875 toddlers. The purpose of this research was to find the correlation of immunization status: DPT-HB-HIB with pneumonia in toddlers (12-24 months) at Babakan Sari community health center Bandung. The research methode was analitic survey with case control approachment, the ratio of case and control categories are 1:1 or 45 cases and 45 controls. The sampling technique was purposive sampling. The instrument in this research was used check list form. Data analysis was univariate and bivariate with chi-square test. The result of this research were imunization status: DPT-HB-HIB (p=0.016; OR=3.946) was related with pneumonia in toddlers (12-24 months). The conclusions in this research indicate that immunization state: DPT-HB-HIB was related with pneumonia in toddlers (12-24 month) at Babakan Sari community health center Bandung. So the results of this research recommend for health workers, especially nurses at Babakan Sari community health center to increase immunization coverage.